2022
DOI: 10.3389/fnut.2022.849005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Relative Abundance of Ruminoccocus Is Associated With Reduced Cardiovascular Risk in an Obese Population

Abstract: BackgroundObesity is a complex disease with underlying genetic, environmental, psychological, physiological, medical, and epigenetic factors. Obesity can cause various disorders, including cardiovascular diseases (CVDs), that are among the most prevalent chronic conditions in Qatar. Recent studies have highlighted the significant roles of the gut microbiome in improving the pathology of various diseases, including obesity. Thus, in this study, we aimed to investigate the effects of dietary intake and gut micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 83 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…Related studies have shown that the relative abundance of Ruminococcus is significantly reduced in populations with obesity and cardiovascular disease risk (Salas-Perez et al, 2023). Ruminococcus plays a key role in the production of SCFAs such as butyric acid through the fermentation of dietary fiber (Lakshmanan et al, 2022). As a type of beneficial bacteria, certain strains of Enterococcus have demonstrated anti-obesity properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies have shown that the relative abundance of Ruminococcus is significantly reduced in populations with obesity and cardiovascular disease risk (Salas-Perez et al, 2023). Ruminococcus plays a key role in the production of SCFAs such as butyric acid through the fermentation of dietary fiber (Lakshmanan et al, 2022). As a type of beneficial bacteria, certain strains of Enterococcus have demonstrated anti-obesity properties.…”
Section: Discussionmentioning
confidence: 99%
“…Limosilactobacillus strains exhibit the ability to modulate energy homeostasis, alter intestinal microbiome composition, synthesize SCFAs, and enhance intestinal barrier function (Abuqwider et al, 2022;Kim et al, 2021). Ruminococcus is the most common bacterium in the gut, capable of producing SCFAs, stabilizing the intestinal barrier (Lakshmanan et al, 2022;Salas-Perez et al, 2023;Zhang et al, 2022), and playing a "cornerstone" role in degrading dietaryresistant starch. Some members of Enterococcus are used as probiotics and participate in the production of acetic acid and propionic acid (Celiberto et al, 2017;Panattoni et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Ruminococcus plays an essential role in the conversion and degradation of complex polysaccharides into nutrients for their hosts (La Reau and Suen, 2018 ). The reduction in the relative abundance of Ruminococcus could increase the risk of cardiovascular diseases in humans ( Lakshmanan et al, 2022 ). In addition, Flavonifractor can metabolize catechin in the gut and help in alleviating antigen-induced Th2 immune responses ( Ogita et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the dietary supplementation of microalgae increased the abundance of Oscillospira. Ruminococcus is one of the dominant bacteria with a dietary fiber fermenting role in producing volatile fatty acids such as butyrate, which is crucial in reducing inflammation and maintaining gut epithelial health ( Lakshmanan et al, 2022 ). Moreover, Ruminococcus is also associated with the production of neurometabolites such as serotonin, norepinephrine, and N-acetyl aspartate, potentially affecting brain function and behavior ( Mudd et al, 2017 ; Lukić et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%